Effect of cold plasma technology on physico chemical and cooking quality parameters of germinated brown rice: Cooking quality of cold plasma treated germinated brown rice - Mohmmed, Naseerunnisa; Kuna, Aparna; Supraja, T; K, Lakshmi Prasanna; Chary, D Srinivasa (ORYZA-An International Journal of Rice, 2025)
Although nutritious, brown rice is hard to chew. Germination and cold plasma technology offer eco-friendly ways to improve its texture and cooking quality. The present study was conducted to investigate the effect of cold plasma technology on the physico-chemical and cooking quality properties of germinated brown rice (GBR) of (RNR 29325- brown rice variety) (Navara- pigmented rice variety). Brown rice (BR) and untreated GBR were considered as control 1 and 2, whereas cold plasma -treated germinated brown rice (CPT GBR) was considered as experimental sample. Cold plasma treatments at 20kV, 25kV and 30kV were induced on raw brown rice (BR) and pigmented rice (PR) at four different time durations (1, 5, 10 and 15 min) each, followed by germination. It was observed that there was significant (P £ 0.005) difference between the L*, a* and b* values among control (BR and untreated GBR) and CPT GBR flours of RNR 29325 and Navara. An increase in plasma voltage and treatment time decreased the amylose content from 16.57±0.87% to 13.95±0.88% and 19.48 ± 0.50% to 14.83±0.88% in RNR 29325 and Navara, respectively. The highest kernel length and breadth after cooking were observed at the longest cold plasma exposure time (15 minutes). The volume expansion ratio ranged from 2.45 ± 0.01 to 2.75 ± 0.01 in RNR 29325, and from 1.98 ± 0.01 to 2.28 ± 0.01 in Navara. A significant (P £ 0.005) increase in water uptake ratio was observed across all the samples in both rice varieties. Cold plasma treatment significantly reduced cooking time-from 36.67 ± 0.58 minutes to 28.00 ± 1.00 minutes in RNR 29325, and from 41.67 ± 0.58 minutes to 32.67 ± 0.58 minutes in Navara. Our study showed that cold plasma improved whole grain texture by lowering amylose content and reducing cooking time.